Of mice and men and women: Sexual dimorphism of the gut microbiome - Jean S. McGee, MD, PhD; Curtis Huttenhower, PhD (Wolters Kluwer, 2021)
The gut microbiome plays a critical role in developing and educating our immune system. Therefore, its now well-established role in autoimmunity and immune disorders is in some ways not surprising. However, it is well-documented in the literature that there is a female predisposition to autoimmune disorders, while sexual dimorphisms in the human microbiome have been confined largely to areas outside of the gut. Herein, we will review the evidence of sexual dimorphism in the gut microbiome in both mice and humans, how this differs in animal models versus humans, and how such dimorphisms may be established and influenced by both host and environmental factors. We will conclude with a discussion on how these aspects of the gut microbiome may contribute to both the study and pathogenesis of gender-specific autoimmunity and immune disorders.